Germline determinants of clinical outcome of cutaneous melanoma. (3rd November 2015) - Vogelsang, Matjaz; Wilson, Melissa; Kirchhoff, Tomas
Summary: Cutaneous melanoma (CM) is the most lethal form of skin cancer. Despite the constant increase in melanoma incidence, which is in part due to incremental advances in early diagnostic modalities, mortality rates have not improved over the last decade and for advanced stages remain steadily high. While conventional prognostic biomarkers currently in use find significant utility for predicting overall general survival probabilities, they are not sensitive enough for a more personalized clinical assessment on an individual level. In recent years, the advent of genomic technologies has brought the promise of identification of germline DNA alterations that may associate with CM outcomes and hence represent novel biomarkers for clinical utilization. This review attempts to summarize the current state of knowledge of germline genetic factors studied for their impact on melanoma clinical outcomes. We also discuss ongoing problems and hurdles in validating such surrogates, and we also project future directions in discovery of more powerful germline genetic factors with clinical utility in melanoma prognostication.